Searching for the credibility of monetary policy in Turkey: Evidence from structural VAR analysis - ALKAN, Buket (Journal of Economics and Political Economy, 2019)
Abstract. A relationship between the macro shocks and the long-term inflation expectations leads to questioning the credibility of a central bank. This paper investigates the credibility of the Central Bank of Turkey by analyzing the anchoring effect of the long-term inflation expectations by using the uncertainty indicator. We conduct the analysis with the structural VAR method using survey-based inflation expectations data as well as economic uncertainty index data developed for the Turkish economy. Our results provided evidence in favor of the existing de-anchoring process and imply that the monetary policy is not fully credible in Turkey during the period under investigation. Keywords. Inflation expectations, Structural VAR, Credibility, Anchoring, The Turkish economy, Uncertainty. JEL. E52, E58.